Intestinal absorption of BCS class II drugs administered as nanoparticles: A review based on in vivo data from intestinal perfusion models - David Dahlgren; Erik Sjögren; Hans Lennernäs (International Association of Physical Chemists (IAPC), 2020)
An established pharmaceutical strategy to increase oral drug absorption of low solubility-high permeability drugs is to create nanoparticles of them. Reducing the size of the solid-state particles increases their dissolution and transport rate across the mucus barrier and the aqueous boundary layer. Suspensions of nanoparticles also sometimes behave differently than those of larger particles in the fed state. This review compares the absorption mechanisms of nano- and larger particles in the lumen at different prandial states, with an emphasis on data derived from in vivo models. Four BSC class II drugs-aprepitant, cyclosporine, danazol and fenofibrate-are discussed in detail based on information from preclinical intestinal perfusion models.